When Voicelessness Meets Speechlessness – Struggling for Equity in Chinese-Ghanaian Employment Relations - Karsten Giese; Alena Thiel (German Institute of Global and Area Studies (GIGA), 2012)
In this article Chinese-Ghanaian employment relations are analyzed using the concepts of foreignness, the psychological contract, equity, and cross-cultural communication. Based on a qualitative study conducted in Accra, Ghana, we discuss the labor market in general and introduce the conditions under which Chinese sojourners operate their family trade businesses in the city. After discussing the phenomenon of Ghanaian employment within Chinese trade companies from a theoretical perspective, we explain how Chinese employers' and Ghanaian employees' culturally based perceptions of employment relations are contradictory and prone to conflict. We then show how, under the condition of the employers' foreignness, Ghanaian employees perceive their psychological contracts as being violated and Chinese employers regard the equity of exchange relations as distorted. We discuss how Ghanaian employees cope with this situation by means of voice, silence, retreat or destruction, while Chinese employers, who lack both sufficient language skills and effective sanctions, choose to endure perceived distortions of equity and in some cases ultimately terminate employment relations when inadequate cross-cultural communication results in a failure to mediate conflicts.
Keywords: J15; J24; J81; Z1; 330; labor relations; equity; psychological contract; trade; China; Ghana; Chinesen; Auslandsaufenthalt; Arbeitsbeziehungen; Arbeitsrecht; Arbeitnehmerschutz; Ghana